Status Kepemilikan Kios Dalam Pusat Perbelanjaan Yang Dibangun Berdasarkan Kontrak Bangun Guna Serah - Tupamahu, Cheryl Nathania; Berlianty, Teng; Kuahaty, Sarah Selfina (PATTIMURA Law Study Review, 2024)
Build Opreate and Transfer Contract is an alternative project financing by the government which gives management rights to private parties for 30 years and then the land and buildings are completely handed over to the government. Based on this agreement, the construction of a building in the form of a commercial building using land which is a regional property asset requires Building Rights. In its management, the private sector as a cooperation partner is given the right to operate the building, including renting or selling the unit inside. For unit ownership based on a sale and purchase agreement, a Flat Unit Ownership Certificate is issued as legal proof of ownership of the unit. This has an impact on the ownership status of the unit after the end of the Build Operate and Transfer Contract which states that the building is fully owned by the government. The issuance of a Certificate of Ownership Rights for a Flat Unit is based on a Building Rights Certificate, while the issuance of a Building Rights Certificate is based on a Build Operate and Transfer Contract. This shows that the Build Operate and Transfer Contract underlies all the agreements above it so that when it ends, all the agreements above also end.